2014
DOI: 10.1080/0144929x.2013.872189
|View full text |Cite
|
Sign up to set email alerts
|

Composition and role of convergent technological repertoires in audiovisual media consumption

Abstract: This mixed-method research focuses on the growing appropriation of multiple screen devices for audiovisual media consumption. Based on survey measures, we distinguish thee patterns: (a) maintaining the status quo, by mainly drawing upon television, (b) broadening up the repertoire, by extending television with computers and mobile devices, or (c) even replacing television by a computer. Next, we draw upon insights form niche theory, rationalizing media choices in terms of competing gratifications. This perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…In contrast, those in the US were split regarding seeking out information from online sources vs. people, and only two participants in Germany mentioned seeking out information at all, one from an online search and one from a peer. Prior work has suggested that those who rely on people they know well (e.g., friends, family) have lower Internet skill than those who seek information online [47]- [49]. However, our results preliminarily suggest that collectivist identities, in addition to potential variance in Internet skill due to recency of Internet adoption, may also explain variance in security information seeking channels.…”
Section: Influence Of Cultural Contextsupporting
confidence: 37%
“…In contrast, those in the US were split regarding seeking out information from online sources vs. people, and only two participants in Germany mentioned seeking out information at all, one from an online search and one from a peer. Prior work has suggested that those who rely on people they know well (e.g., friends, family) have lower Internet skill than those who seek information online [47]- [49]. However, our results preliminarily suggest that collectivist identities, in addition to potential variance in Internet skill due to recency of Internet adoption, may also explain variance in security information seeking channels.…”
Section: Influence Of Cultural Contextsupporting
confidence: 37%
“…Keempat adalah media displacement, yaitu khalayak beralih dari media lama ke media baru yang lebih terpersonalisasi (personalized) . Media akan dikonsumsi selama masih bisa memenuhi kebutuhan dan khalayak akan berpindah ke media baru jika kebutuhan tersebut tidak terpuaskan (Courtois et al, 2014). Nimrod (2019) menyebut fenomena ini sebagai functional displacement.…”
Section: Pendahuluanunclassified
“…Niche theory applies the three concepts of niche breadth, niche overlap, and niche superiority to examine how two or more populations coexist and compete when there are limited resources in their environment [40][41][42][43]. The concepts of breadth and overlap in ecological niche theory are similar to the concepts of complementary goods and substitutional goods in economics [40,44].…”
Section: Concept Of Niche Theorymentioning
confidence: 99%
“…Therefore, niche superiority is measured to analyze which entity is superior. This analysis develops the results of the analysis of niche overlap, which were only presented as the exchangeability of entities in the use and gratification approach, into the judgment of the superiority of the functions of entities by the subjective evaluation of the user to provide explanations about the condition and the direction of substitution between entities with a high possibility of functional substitution [41].…”
mentioning
confidence: 99%